The Impact of Financial Literacy, Inclusion, and Access on Msme Growth and Welfare in North Sumatra: A Mediating Role of Business Growth - Harahap, Zulkifli Ikhwan; Lubis, Satia Negara; ., Erlina; Aritonang, Evawany Yunita (Journal of Ecohumanism, 2024)
This study examines the impact of financial literacy, financial inclusion, and financial access on the growth and welfare of Micro, Small, and Medium Enterprises (MSMEs) in North Sumatra, Indonesia, with business growth acting as a mediating factor. Using a quantitative research design and Structural Equation Modeling (SEM) analysis, data were collected from 306 MSME operators selected via purposive sampling. The findings reveal that while financial literacy does not have a significant direct effect on MSME growth and welfare, both financial inclusion and financial access significantly enhance business growth and welfare. Furthermore, business growth serves as a mediating variable, amplifying the positive effects of financial inclusion and access on MSME welfare. The results indicate that MSMEs benefit from better access to formal financial services, such as credit and insurance, which facilitates business expansion and improves the overall welfare of business owners. However, the lack of significant impact from financial literacy suggests that practical financial education initiatives should be paired with improved access to capital and market opportunities. This study highlights the need for integrated policy efforts to enhance financial literacy, expand financial inclusion, and provide easier access to credit to foster MSME growth and welfare in North Sumatra.